The Role of Regional Anesthesia During the SARS-CoV2 Pandemic: Appraisal of Clinical, Pharmacological and Organizational Aspects - Cappelleri, Gianluca; Fanelli, Andrea; Ghisi, Daniela; Russo, Gianluca; Giorgi, Antonio; Torrano, Vito; Lo Bianco, Giuliano; Salomone, Salvatore; Fumagalli, Roberto (Frontiers in Pharmacology, 2021)
The severe acute respiratory syndrome coronavirus SARS-CoV2 is spreading over millions of people worldwide leading to thousands of deaths, even among the healthcare providers. Italy registered 154 dead among physicians and 45 among nurses as of May 8, 2020. Anesthesiologists are at higher risk as they are the care providers in both ICU and operating rooms. With the scheduled re-start of the elective surgery (phase 2), physicians will have to cohabitate with the virus and the potential risk of contagion, protecting themselves and the patients from the risks of infection while providing the best care to their surgical patients. Regional anesthesia allows a reduction in airway manipulation, therefore reducing the environmental contamination. Furthermore, regional anesthesia reduces the opioid requirements as well as the muscle paralysis due to muscle-relaxants and should be recommended whenever possible in COVID-19 patients. Our aim is to evaluate the advantages and criticisms of regional anesthesia in the management of surgical patients during the transition from phase-1 to phase-2 of the COVID-19 pandemic.